Proteolytic mechanisms involved in the metastasis of human melanoma cells - Fletcher, Jean Margaret (Division of Chemical Pathology, 2018)
The metastatic process requires that tumour cells are capable of traversing various micro-environmental barriers, such as the basement membrane. There are various proteolytic mechanisms which could contribute to the process, plasminogen activation by tissue plasminogen activator (tPA) and urokinase plasminogen activator (uPA) is one such mechanism. Extensive reports in the literature (reviewed in the introduction) indicate that most tumour cells synthesize uPA and that it is this enzyme, particularly when receptor-bound, which plays a role in invasion. UCT-Mel 3 is a human malignant melanoma cell line which was established in our laboratory, and has been shown to be highly metastatic in the nude mouse. This cell line is typical of many melanomas in that it synthesizes only tPA and not uPA. In part 1 of this thesis I further investigated the plasminogen activator production by these cells (at the level of mRNA as well as activity) as well as expression of plasminogen activator inhibitor PAl-1 and receptors for tPA and uPA (uPAR). UCT-Mel 3 cells expressed uPAR although uPA was not detected. I also examined cells cultured from two metastatic deposits. Interestingly, the metastatic cells produced PAl-1 which was undetected in the parent cells. After confirming that UCT-Mel 3 do not express detectable levels of uPA, I attempted (in part 2) to determine whether tPA could play a comparable role to that of uPA in the invasive process. My strategy was to inhibit the expression of tPA via two different methods, namely the use of antisense RNA and ribozyme. I then hoped to isolate clones producing no tPA, which would have been injected into nude mice in order to assay for metastasis. Unfortunately, neither of these methods proved to be successful in abrogating tPA expression. I was thus unable to achieve the ultimate aim of the project. However, during the course of the study a number of unforeseen problems arose. Firstly, the clonal variation within the cell population, and secondly, my inability to obtain antisense transfectants. I have speculated that a possible reason for the latter may be that the cells are in fact unable to grow in the absence of tPA.